2017
DOI: 10.1007/s00216-017-0467-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profiling of carbamazepine and ibuprofen in Solea senegalensis bile using high-resolution mass spectrometry

Abstract: The widespread occurrence of pharmaceuticals in the aquatic environment has raised concerns about potential adverse effects on exposed wildlife. Very little is currently known on exposure levels and clearance mechanisms of drugs in marine fish. Within this context, our research was focused on the identification of main metabolic reactions, generated metabolites, and caused effects after exposure of fish to carbamazepine (CBZ) and ibuprofen (IBU). To this end, juveniles of Solea senegalensis acclimated to two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Interestingly, we were able to detect a second bioTP of CBZ, CBZ-DH, through analysis of the exposure medium. CBZ-DH is formed from CBZ-Ep, facilitated by soluble epoxide hydrolase (sEH) enzymes, and has been previously reported to form in fish. , One of these studies found sEH in high quantities in the liver, kidney, and gills of rainbow trout (Salmo gairdneri). The discrepancy in CBZ-DH formation could indicate that epoxide hydrolase activity is low or nonpresent in liver microsome extracts, possibly through sEH inactivation during the preparation of the microsome extract because CBZ-DH is predominantly biotransformed in the gills, kidneys, or a combination of the two.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we were able to detect a second bioTP of CBZ, CBZ-DH, through analysis of the exposure medium. CBZ-DH is formed from CBZ-Ep, facilitated by soluble epoxide hydrolase (sEH) enzymes, and has been previously reported to form in fish. , One of these studies found sEH in high quantities in the liver, kidney, and gills of rainbow trout (Salmo gairdneri). The discrepancy in CBZ-DH formation could indicate that epoxide hydrolase activity is low or nonpresent in liver microsome extracts, possibly through sEH inactivation during the preparation of the microsome extract because CBZ-DH is predominantly biotransformed in the gills, kidneys, or a combination of the two.…”
Section: Resultsmentioning
confidence: 99%
“…(Data not shown). Moreover, these degraded products are expected to further accumulate in water bodies via biotic and abiotic mechanisms (Aceña et al, 2017). Thus, the implications discussed in this work, degradation and toxicological effects, are transferable to the environmentally-relevant conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding biotransformation enzymes, glutathione S-transferases (GSTs) are Phase II enzymes known to be involved in xenobiotic detoxification by catalysing hydrophobic and electrophilic molecules when conjugated with glutathione, making them less toxic and thus more easily eliminated (Allocati et al, 2018). Carboxylesterases (CEs) are Phase I hydrolytic enzymes well-known for pesticide detoxification and the metabolic transformation of some pharmaceutical drugs (Acena et al, 2017;Solé et al, 2018). In the present study, no significant differences were observable between the activity of biotransformation enzymes of contaminated and non-contaminated organisms, highlighting the absence of a response of T. reticulata to Li.…”
Section: Tablementioning
confidence: 99%